Análise de um modelo de dimensionamento da força de trabalho dos servidores técnico-administrativos da UFPA com ênfase na gestão por competência - ALMEIDA, Walquiria Corrêa de (Universidade Federal do Pará, 2019)
Scale an organization's server framework is a task of the most significant area of human resources, however, difficult to implement, since account the work force may not be enough to put people trained in strategic locations or with specific profiles to meet organization's needs. From 2005, with the implementation of the Plan of Careers of technical and administrative positions of Education Federal Institutions, the staff dimensioning it became mandatory task for efficient management, for the preparation of the Technical Development Plan, approved in 2006 requires the adequacy of the server framework from a model of allocation of positions. In the same year of the Technical Career Plan the Federal Government launched the guidelines for implementation of the National Staff Development Policy federal government and brought to the public service, management by competence, whose purpose is to provide improved services to citizen, emphasizing the efficiency, effectiveness through the ongoing development of the server and the adequacy of their skills to the organization's objectives. Considering this context, the research in question had an exploratory nature to seek to discuss the integration of Management Skills with the subsystem staff dimensioning, and, if used the skills mapping to map the skills and delivery of crowded servers in Program graduate of UFPA, in order to qualitatively assist the design. Deliveries were also tested as quantitative variable for use in the calculation matrix. The quantitative results were obtained by means of descriptive statistics, raising the profile of the servers in relation to the link with the UFPA, education, length of service and hours of work. To calculate the matrix was used measures of central arithmetic average and median tendency to check the ideal framework server with the application of the data in a model already used by the UFPA to scale the technical and administrative staff. The work resulted in the mapping of competence and deliveries and staff dimensioning of the secretariats of graduate programs